2014
DOI: 10.1016/j.rmed.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prediction of pulmonary hypertension in severe emphysema

Abstract: Mildly elevated pulmonary artery pressures are found in a significant proportion of patients with severe emphysema. However, severe PH is uncommon in the absence of co-morbidities. Simple non-invasive tests may be helpful in screening patients for pre-capillary PH in severe emphysema but none is reliably predictive of its presence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
0
20
1
4
Order By: Relevance
“…This might be hampered by the lack of echocardiographic data in 130 patients. Not only has research shown a high prevalence of PH in COPD patients [35,36], but PH is also known to be of importance in NCFB as right ventricular dysfunction and right ventricular dimensions are greater in cystic NCFB and are positively correlated with systolic pulmonary artery pressure and negatively correlated with partial pressure of oxygen in arterial blood. In more severe NCFB, there is an impaired perfusion with more capillary bed destruction and left-to-right shunt, leading to impaired cardiac function and pulmonary gas exchange [37].…”
Section: Discussionmentioning
confidence: 99%
“…This might be hampered by the lack of echocardiographic data in 130 patients. Not only has research shown a high prevalence of PH in COPD patients [35,36], but PH is also known to be of importance in NCFB as right ventricular dysfunction and right ventricular dimensions are greater in cystic NCFB and are positively correlated with systolic pulmonary artery pressure and negatively correlated with partial pressure of oxygen in arterial blood. In more severe NCFB, there is an impaired perfusion with more capillary bed destruction and left-to-right shunt, leading to impaired cardiac function and pulmonary gas exchange [37].…”
Section: Discussionmentioning
confidence: 99%
“…We also collected survival data. We calculated the FEV 1 /D LCO , which has been shown to be a potential predictor of precapillary PH in COPD patients [16]. …”
Section: Methodsmentioning
confidence: 99%
“…In a recent study looking at 797 patients enrolled in the NETT trial who received right heart catheterization, only 2.2 % had severe PH, defined by a mean PAP > 35 mmHg. Interestingly severe pulmonary hypertension, often defined by echo, was an exclusion criteria for this trial (Minai et al 2014). Other studies show a prevalence of 1-10 % depending on whether severe PH is defined as a mPAP of 35 or 40 mmHg (Thabut et al 2005;Scharf et al 2002;Chaouat et al 2005).…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 97%